ANALISIS KUALITAS SALA TERI - Fitri, Annisa Eka; Faridah, Anni; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research was aimed to analyze the effect of used 0 g, 20 g, 40 g, 60 g and 80 g anchovies toward the quality of shape, color, aroma, texture and taste of the anchovies fish ball. This research was an experiment research which used completely randomized design method. This research was conducted on August in a workshop Culinary Art Department of IKK, FPP, UNP. The independent variable was anchovies and the dependent variable was the quality of anchovies fish ball. The type of data was primary data sourced from 30 panelists who fill the organoleptic format to sample. Analysis of Varian was used to analyze the data if Fcount> Ftable then continued by Duncan test. The results showed that the amount of used teri affected the quality of color, anchovies aroma, and flavor. While in shape, it had no significant effect toward the fragrant aroma and texture of anchovies. The highest score is the shapes (round) 3,19 (60 gr), form (one kind) 2.98 (60 gr), outside color (golden yellow) 3,08 (20 gr), inside color (yellow) 3,17 (20 gr), aroma (anchovies) 3.44 (80 gr), aroma (fragrant) 3.07 (80 gr), outside texture (crunchy) 2.98 (60 gr), inside texture (hollow) 2.78 (60 gr), and the quality of taste (savory) 3.22 (80 gr). The best results of anchovies fish ball quality was 60 grams.Key word : Fish Ball, Anvhovies, Quality, Analysis